NEW INSIGHTS OF MAMMARY GLAND DURING DIFFERENT STAGES OF DEVELOPMENT - Jena, Manoj Kumar; Mohanty, Ashok Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Mammary gland is a unique organ with its function of milk synthesis, secretion, and involution to prepare the gland for subsequent lactation. The mammary epithelial cells proliferate, differentiate, undergo apoptosis, and tissue remodeling following a cyclic pathway in lactation â€“ involution â€“ lactation cycle, thus fine tuning the molecular events through hormones, and regulatory molecules. Several studies are performed on the mammary gland development, lactogenesis, and involution process in molecular details. The developmental stages of mammary gland are embryonic, pre-pubertal, pubertal, pregnancy, lactation, and involution. Major developmental processes occur after puberty with hormones and growth factors playing crucial role. The two major pathways such as Janus kinases-signal transducer and activator of transcription pathway and PI3K-Akt pathway play a major role in maintaining the lactation. The involution process is a well-orchestrated event involving several signaling molecules and making the gland ready for subsequent lactation. The review focuses on findings with molecular details of different stages of the mammary gland development and signaling pathways involved in lactationâ€“involution cycle. Deep insight into the developmental stages of mammary gland will pave the way to understand mammary gland biology, apoptosis, oncogenesis, and it will help the researchers to use mammary gland as a model for research on various aspects. Â